Analisa Perbandingan Konstruksi Jalan Perkerasan Lentur Dengan Perkerasan Kaku Ditinjau Dari Metode Pelaksanaan Dan Biaya (Studi Kasus: Pekerjaan Peningkatan Struktur Jalan Mantingan-Ngawi) - Sahrianto, Lutfi Ana; , Senja Rum Harnaeni, S.T., M.T; , Ir. H. Muhammad Nur Sahid, M.M., M.T (2016)
Road is one of the ground connect facility which had an important role play in the in human life. One of the support is their displacement or mobilization from one place to another. In road construction costs that much. Therefore we need good planning and appropriate standards in order to get the effective, efficient and economical result. This final task is made to evaluate at the same time a comparison between the use of flexible pavement road construction use drainage channels cast in place by way of rigid pavement using precast drainage channel construction on road improvement project between Mantingan to Ngawi. This study compares the two packages the job in terms of cost and methods of implementation. Comparison of road construction are centered on the cost of pavement and leveling along the 2 km, while the cost of drainage channels focused on each of the main construction along 850 m. In this event research method divided into four stages: the first stage is the study of literature and the initial survey, the second stage of secondary data collection to support the research, the third stage analysis of the discussion of each job and the fourth stage is the conclusions and suggestions from the discussion. From the analysis that has been done, for the work package using the flexible pavement road construction drainage channels cast in place at a cost of Rp. 11,970,576,399.00, whereas for rigid pavement work packages using precast drainage channels at a cost of Rp. 16.684.481.501.00, including 10% of tax. The difference in terms of implementation methods between work flexible pavement and jobs rigid pavement found in the work of compaction, the flexible pavement compaction is done with three stages (compaction, intermediate rolling and finishing rolling), while the rigid pavement compaction is done with the first phase (with vibrator only). For flexible pavement construction does not use the framework, while the rigid pavement requires framework. At the flexible pavement construction does not require a wait of age, whereas in rigid pavement construction requires a wait of age (aged concrete ± 28 days).